2013
DOI: 10.1007/s00774-013-0438-9
|View full text |Cite
|
Sign up to set email alerts
|

Pamidronate treatment stimulates the onset of recovery phase reducing fracture rate and skeletal deformities in patients with idiopathic juvenile osteoporosis: comparison with untreated patients

Abstract: Although spontaneous remission occurs in patients with idiopathic juvenile osteoporosis (IJO), permanent bone deformities may occur. The effects of long-term pamidronate treatment on clinical findings, bone mineral status, and fracture rate were evaluated. Nine patients (age 9.8 ± 1.1 years, 7 males) with IJO were randomized to intravenous pamidronate (0.8 ± 0.1 mg/kg per day for 3 days; cycles per year 2.0 ± 0.1; duration 7.3 ± 1.1 years; n = 5) or no treatment (n = 4). Fracture rate, phalangeal quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Many studies have demonstrated beneficial outcomes with pamidronate treatment in children with OI [1][2][3], as well as other bone fragility conditions such as idiopathic juvenile osteoporosis [4], spastic quardriplegic cerebral palsy [5][6][7], neuromuscular disorders [8], steroids-induced osteoporosis [9], and fibrous dysplasia [10]. Bisphosphonates decrease bone turnover by decreasing bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated beneficial outcomes with pamidronate treatment in children with OI [1][2][3], as well as other bone fragility conditions such as idiopathic juvenile osteoporosis [4], spastic quardriplegic cerebral palsy [5][6][7], neuromuscular disorders [8], steroids-induced osteoporosis [9], and fibrous dysplasia [10]. Bisphosphonates decrease bone turnover by decreasing bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with osteogenesis imperfecta, improved or no effect on linear growth is reported [84]. In patients with IJO, a normal pattern of linear growth during long-term intravenous pamidronate treatment was found [5]. …”
Section: Adverse Effects Of Bisphosphonates In Pediatric Patientsmentioning
confidence: 99%
“…A schematic representation of bisphosphonate effects on bone cells is depicted in figure 2. The positive effect of bisphosphonates on bone formation, even in the face of reduced overall bone remodeling, could explain part of the antifracture efficacy and bone mass recovery in patients with idiopathic juvenile osteoporosis (IJO) during pamidronate treatment [5]. Table 1 shows the chemical structure, route of administration, dose range, and potency relative to etidronate of the main bisphosphonates used in pediatric patients.…”
Section: Structure and Mechanisms Of Action Of Bisphosphonatesmentioning
confidence: 99%
See 2 more Smart Citations